Utility Of Three-Dimensional Heads-Up Surgery In Cataract And Minimally Invasive Glaucoma Surgeries - Ohno H (Dove Medical Press, 2019)
Hisato Ohno Ohno Eye Clinic, Asaka, Saitama, JapanCorrespondence: Hisato OhnoOhno Eye Clinic, 2-14-18 Nishihara, Asaka, Saitama 351-0034, JapanTel +81 48 424 3733Fax +81 48 424 5571Email vitrectman@ohno-eye.comPurpose: This study aimed to assess the utility of the three-dimensional (3D) heads-up visualization system for minimal incision cataract surgery (MICS) and minimally invasive glaucoma surgeries (MIGSs).Methods: Toric intraocular lens (IOL) implantation with phacoemulsification and trabecular microbypass stent implantation in patients with cataract and open-angle glaucoma were performed using the heads-up 3D visualization system combined with surgical navigation rather than the conventional microscope.Results: This procedure was found to have the following advantages: the ability to clearly observe the anterior chamber angle image without requiring frequent focus adjustment owing to the extended depth of field and emphasized stereoscopic effect provided by this system and maintain the surgeon’s posture.Conclusion: The feasibility and comfort of this system are greater than those of the conventional microscopic for performing MICS and MIGS.Keywords: toric intraocular lens, phacoemulsification, open-angle glaucoma